Pengaruh Bauran Pemasaran Syariah Terhadap Loyalitas Jamaah Umrah Di PT. Ikhwan Berkah Sejahtera - Putri, Sayyidah; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2019)
The aim of this research is to test the effect of marketing mix sharia (product, price, promotion, place, people, process, and physical evidence) towards loyalty of Umrah pilgrims in PT. Ikhwan Berkah Sejahtera. This research was conducted with an associative quantitative approach. Number of samples that used in this research is 93 respondents which came from umrah pilgrims 2017-2018 period and used simple random sampling technique. This research used a questionnaire that calculates with a likert scale and analyzed with SPSS 23. The result of this research shows that overall marketing mix sharia variable has a positive effect and significant to the loyalty of Umrah pilgrims. Based on the partial test result indicates that there are 2 positive effect variables and significant towards loyalty of Umrah pilgrims, that is promotion variable and process. As for based on the coefficient of determination test’s result, shows that marketing mix sharia variable have a big impact as big as 41,3% against loyalty of Umrah pilgrims’ variable